Pengaruh Aktivitas Fisik terhadap Kebugaran Siswa SMP IT Almunadi Medan - M Fadlin Al Farhans; Mesnan; Nurhayati Simatupang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of physical activity on the fitness of students at SMP IT Almunadi Medan. The research method used is a quasi-experimental, with a